2022
DOI: 10.3389/fphys.2022.1021927
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout integrated response after recovery from short-term acute hypoxia

Abstract: Overcoming a stress situation, such as hypoxia episodes, which involve an allostatic load, will depend on the ability of fish to modulate physiological and biochemical systems to maintain homeostasis. The aim of the study was to determine the integrated stress response after acute hypoxia of the rainbow trout considering the different elements and areas of the stress response: systemic and mucosal, local and global, and from the systemic hypothalamic–pituitary–interrenal axis to skin mucosa. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…In fish, both gsr and g6pd have been studied extensively. For example, a study on gsr gene in rainbow trout showed that its expression was induced by oxidative stress caused by exposure to pollutants (García-Meilán et al, 2022). Another study on zebrafish found that gsr gene expression was higher in liver tissues of fish exposed to high levels of heavy metals (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fish, both gsr and g6pd have been studied extensively. For example, a study on gsr gene in rainbow trout showed that its expression was induced by oxidative stress caused by exposure to pollutants (García-Meilán et al, 2022). Another study on zebrafish found that gsr gene expression was higher in liver tissues of fish exposed to high levels of heavy metals (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%